ADAPTASI BANGUNAN DI UNIVERSITAS NEGERI MANADO - Muhammad Muhdi Attaufiq; Misran Rahman (Universitas Negeri Gorontalo, 2023)
The condition of the educational environment affects the continuity of the learning process. Therefore, the existence and adaptation of the form of buildings to the comfort of learning becomes a forum in supporting the development of science and the development of students so that they are influential in the world of education. Some principles of adaptation to the physical conditions of the environment are carried out in response to changes that occur in the environment. By using the observation method of changing conditions, changes in the shape of rooms and buildings will be seen in order to adapt to changes in the learning room